South Africa’s Curriculum Transformation: Insights from Post-Independence Africa and Post-Civil Rights Movement in the United States (The Strategic Review for Southern Africa, 2021)
The #MustFall campaigns, student-led protests that began at the University of Cape Town (UCT) in 2015 and reverberated across South African universities, ignited calls for curriculum transformation, the abolition of Eurocentric epistemologies, and the embrace of indigenous knowledge systems. Given that despite more than two-and-a-half decades of majority rule, South African universities continue to promote hegemonic Western thought, the call for genuine curriculum transformation is understandable. Against this backdrop, this article investigates the challenges associated with curriculum transformation efforts in South Africa. It offers potential solutions by drawing lessons from transformation efforts in the humanities in postcolonial African states and African-American studies in the civil rights movement in the United States (US).